Given:

\(\displaystyle{3}\sqrt{{{64}{\left({x}+{6}\right)}}}\)

Recall that

\(\displaystyle\sqrt{{{a}^{{2}}{b}}}={a}\sqrt{{b}}\)

In our case, \(\displaystyle{a}={64},{\quad\text{and}\quad}{64}={8}^{{2}}\), so

\(\displaystyle{3}\sqrt{{{64}{\left({x}+{6}\right)}}}={3}\times{8}\sqrt{{{x}+{6}}}\)

Multiply:

\(\displaystyle{3}\times{8}\sqrt{{{x}+{6}}}={24}\sqrt{{{x}+{6}}}\)

The final answer:

\(\displaystyle{3}\sqrt{{{64}{\left({x}+{6}\right)}}}={24}\sqrt{{{x}+{6}}}\)

\(\displaystyle{3}\sqrt{{{64}{\left({x}+{6}\right)}}}\)

Recall that

\(\displaystyle\sqrt{{{a}^{{2}}{b}}}={a}\sqrt{{b}}\)

In our case, \(\displaystyle{a}={64},{\quad\text{and}\quad}{64}={8}^{{2}}\), so

\(\displaystyle{3}\sqrt{{{64}{\left({x}+{6}\right)}}}={3}\times{8}\sqrt{{{x}+{6}}}\)

Multiply:

\(\displaystyle{3}\times{8}\sqrt{{{x}+{6}}}={24}\sqrt{{{x}+{6}}}\)

The final answer:

\(\displaystyle{3}\sqrt{{{64}{\left({x}+{6}\right)}}}={24}\sqrt{{{x}+{6}}}\)